Comparative study evaluating efficacy of sufentanil versus midazolam in preventing myoclonic movements following etomidate - Mohammad Alipour; Masoumeh Tabari; Azadeh Mokhtari Azad (Wolters Kluwer Medknow Publications, 2016)
Background and Aims: Myoclonus is a major side-effect following etomidate injection requiring use of medical intervention. Material and Methods: In this double-blinded clinical trial, 50 consecutive patients, randomly received sufentanil 0.2 μg/kg or midazolam 0.015 mg/kg, 90 s before induction of anesthesia with etomidate (0.3 mg/kg). Then, the patients were monitored for any myoclonic movements during anesthesia. Results: The incidence of myoclonus was 28% in the sufentanil group and 84% in the midazolam group. The frequency and intensity of myoclonus were significantly higher in the midazolam group, compared to the sufentanil group (P < 0.001). Myoclonus duration in the sufentanil and midazolam groups were 5.8 ± 13.2 and 69 ± 47.8 s, respectively (P < 0.0010). Conclusion: The frequency, intensity and duration of myoclonus in the midazolam group, were significantly more prevalent than the sufentanil group.